Cytotoxicities of xanthones and cinnamate esters from Hypericum hookerianum - Rujida Wilairat (2018)
5-Hydroxy-2-methoxyxanthone (1), 2-hydroxy-3-methoxyxanthone (2), trans-kielcorin (3), 4-hydroxy-3-methoxyphenyl ferulate (4) and 3β-O-caffeoylbetulinic acid (5) were isolated from Hypericum hookerianum. Compounds 1-5 were tested against the growth of three human tumor cell lines, MCF-7, NCI-H460 and SF-268. Compounds 4 and 5 exhibited significant inhibitory activity effects against all three; GI50values for 4 were 15.1 ± 1.6, 18.7 ± 2.3 and 15.9 ± 2.7 and for 5 12.2 ± 2.4, 19.6 ± 2.3 and 24.3 ± 2.5. Compound 3 was less active with GI50values of 55.1 ± 2.3, 49.7 ± 3.0 and 40.5 ± 1.5, while 1 and 2 exhibited only weak effects. Compounds 4 and 5 were moderately effective in influencing the mitogenic response to human lymphocytes to hemoagglutinin, with IC values of 26.1 ± 3.6 and 40.8 ± 4.9, respectively. copy; Georg Thieme Verlag KG Stuttgart.